Immersive feature through 360º video in Spanish news media - Benítez De Gracia, María José (2018)
This paper offers the results of a content analysis on how Spanish media are using the 360º video feature. Unlike other conventional ways of storytelling, this new modality provides the viewer with a sensation of being really present in a reality that is only being represented, which favors a deeper and more meaningful understanding of it. The study consists of a sample of 147 360º video features produced by 19 Spanish media between January 2015 and December 2017. The results confirm a slight increase in the number of publications in 2017 and a preference for using this format to cover social issues. The main purpose of these features seems to be to show the events in their context. The use of the several techniques to increase the sense of presence is still low.